Care of older people with diabetes : a manual for healthcare practice - Sinclair, Alan; Abdelhafiz, Ahmed (Wiley-Blackwell, 2025)
"Building on the reputation of the first four textbooks of Diabetes in Old Age, the new formatted version brings together the top global experts in the field to provide shortened and more concise chapters that are formatted as Background, Key Facts, Key Management aspects, up to 20 key references, two case histories with model answers, and a website link showing a video of a functional assessment. New diabetes complications such as frailty, sarcopaenia, and dementia will be covered as well as the application of new technologies that assist diabetes self-care and monitoring of diabetes"--